A study on the sexual health and menopause - Rohini Jaggi; Pratyaksha Raina; Neha Majortra (Barpeta Obstetrics and Gynaecological Society, 2022)
Objectives: To evaluate the effect of menopause on the sexual health of middle-aged and older women and to determine the association of sexual dysfunction with menopausal symptoms. Methods: This prospective observational cross-sectional study included 100 married sexually active menopausal women visiting gynaecology OPD or admitted in gynaecology wards of the department during the study period 2017-2018. Three questionnaires including demographic, menopause rating scale (MRS) and female sexual function index (FSFI) were used. The higher score means the better the sexuality. A score lower than 26.55 is considered the cut-off value for the diagnosis of female sexual dysfunction. Data reported as mean ± standard deviation and proportions as deemed appropriate for quantitative and qualitative variables respectively. Results: Mean duration of menopause was 10.37 ± 6.63 with a range of 0 to 26 years. The mean somato-vegetative symptom score was 4.98 ranging from 1 to 12. Most subjects had total symptom scores of 16-20 (30%) indicating a higher degree of complaints, followed by 5-10 (29%), 11-15 (28%) and scores of >21 (13%). According to FSFI domain scores, domain of arousal had the least mean score of 1.40, followed by desire at 1.92, lubrication at 2.20, orgasm at 2.64, pain at 3.04 and satisfaction at 3.23. Mean full scale score of 14.46 with a range of 4.9-22 indicate that all 100 subjects carried the symptoms of female sexual dysfunction. Mean value of FSFI full scale score was low in >16 score group (12.93) as compared to that of <16 score group (15.05), the difference being statistically highly significant (p=0.006). Higher psychological symptom score yielded lower FSFI mean scale score, subjects with high somato-vegetative symptom scores had low FSFI mean scale score. The results indicated that altogether all subjects were affected by urogenital and sexual symptoms. Conclusion: Sexually active women experience sexual dysfunction significantly and severity of menopausal symptoms in somatic and urogenital dimensions is associated with sexual dysfunction. It is important to recognize sexual concerns well in time so that appropriate medical treatment can be prescribed as there is high percentage of sexual desire and arousal disorder during the menopausal period.